Unified Decoupling Vector Control of Five-Phase Permanent-Magnet Motor With Double-Phase Faults - Cheng Chen; Huawei Zhou; Guanghui Wang; Guohai Liu (IEEE Access, 2020)
Multi-phase permanent-magnet (PM) motor is a competitive candidate for application where uninterrupted operation is demanded under fault condition. However, double-phase open-circuit or short-circuit faults result in serious problems, such as high fluctuating-torque, deteriorated dynamic performance, even breakdown. This paper proposes a novel unified decoupling vector control strategy to restrain torque fluctuations and improve dynamic performance for a five-phase PM motor with arbitrary double-phase failures. The novelty of the proposed strategy is the development of reduced-order orthogonal transformation matrices and remedies voltages, and then the smooth operation with vector control strategy can be achieved under double-phase open-circuit or short-circuit fault condition. The decoupled motor model in the synchronous rotating frame is achieved by the combination of the reduced-order orthogonal transformation matrices deduced from the optimal fault-tolerant currents and the remedy voltages. The torque fluctuations cancellation is achieved by the remedy voltages. This control strategy exhibits the improved dynamic performance with smooth torque of the faulty PM motor. The experimental results are presented to verify the feasibility of the proposed strategy.